Otelo - o mouro de Veneza, de Shakespeare: crítica e tradução literária - Tavares, Enéias Farias (2007)
The play Othello - The moor of Venice by Shakespeare has had several translations in Brazil. Some of the translators are Onestaldo of Pennafort, Carlos Alberto Nunes, Barbara Heliodora and Beatriz Viegas-Faria. While Pennafort, Nunes and Heliodora translated the play using a ten-syllable verse, Viégas-Faria translated the tragedy in prose. The aim of this study is to analyze the reviews and the translations of the play in order to think about new possibilities of poetic translation of this Shakespearean play. This master's thesis, entitled "Othello The moor of Venice: Literary Criticism and Translation", is divided in five chapters. In the first chapter, "Sources and influences of the play", the main themes used by Shakespeare to compose his tragedy such as the medieval moralities; the Italian tale by Cinthio; the Italian characters of the Commedia Dell'Arte and the Elizabethan/Jacobean idea about the moors are analyzed. In the second, "Othello criticism: a study of the characters in the tragedy", a discussion based on the opinion of the main reviewers of the play is proposed. In the third chapter, "The psychological change in the discourse of the protagonist of Othello", the focus is on the changes that the protagonist's language goes through as his suspicion develops. In the fourth chapter, entitled "Between the Shakespearean prose and verse: Brazilian translations of Othello", the history of the play in Brazil is presented through the discussion of the four translations of it made into Portuguese. In the last chapter, "A new poetic translation of Othello - The moor of Venice: among the tragic, the comic and the lyric", the poetical and sonorous choices of metrics used in this new translation are described. Also the results of this translation, in which the thematic and stylistic variations of the tragedy become clear, are presented. Finally, there are four appendices to complement this work. In appendix A, there is important information on Shakespeare's play; in appendix B, my translation of the Cinthio's tale, used by Shakespeare to compose his drama, is presented; in Appendix C, there are images of the period in which Othello was written and pictures of some actors that played different roles in the tragedy. Finally, in appendix D, the first translation made by me of Othello The moor of Venice is presented.